Pendampingan Belajar Himpunan Matematika Untuk Siswa-Siswi Kelas VII SMP Kristen 03 Kalabahi - Marta Outang; Jeni Marianti Loban; Jon Idrison Molina; Elen A. Hinadang; Yuliana A. Mowata (Yayasan Literasi Sains Indonesia, 2023)
The community service activities carried out were in the form of learning assistance for class VII students of junior high school (SMP) Christian Middle School 03 Kalabahi. This activity aims to increase students' understanding, enthusiasm and enthusiasm for learning mathematics, especially in mathematics set material. From the results of observations and identification carried out in the first week, it was found that interest in mathematics was quite low, this was known through the initial tests conducted. The results of the initial test (pre-test) are known that most of the students have not completed or obtained test scores below the minimum competency score. The results of these findings were then discussed together to design mentoring activities, the results of the pre-test were also the basis for us to carry out learning assistance, with the hope that students could increase their interest in learning mathematics and increase their grades in mathematics. After learning assistance for some time then a final test is carried out to evaluate the process that has been carried out, from the results of the final test (post test) a change is obtained in the grades obtained by each student when compared to the initial test (pre test).